THE STRATEGY OF HOUTHIS TO SEIZE CONTROL OF YEMEN'S TERRITORY: DISTORTION OF SOCIAL NORMS IN CONFLICT - Nety Novita Hariyani; Arina Haque; Wildana Wargadinata; Muflikhah Ulya (Arabic Literature Department, 2022)
The Houthis' attempt at seizing control of Yemeni territory initially seemed like a protest against the presence of power. However, the Houthi rebellion grew louder and bolder until it crossed the boundaries of social norms. The Houthi group's efforts experienced increasing strong power dynamics, leading to a rising severe conflict. In line with the background, the researchers formulated three problem formulations: (1) How did the Houthis begin their efforts to seize control of Yemen's territory? (2) What are the factors that make the strategy of the Houthis a distortion of social norms in the conflict? (3) How do the dynamics of the Houthi power over Yemen play out in the distortion of social norms? This research is based on the argument that the Houthis are trying to distort social norms in Yemen. This research is a qualitative descriptive study. The technique used in data collection is reading and taking notes. The data analysis techniques in this study are data reduction, data presentation, and conclusion. This research indicates that the conflict between the Houthis and Yemen is an organized conflict of interest.